Methylation status of nc886 epiallele reflects periconceptional conditions and is associated with glucose metabolism through nc886 RNAs - Marttila Saara; Viiri Leena E.; Mishra Pashupati P.; Kühnel Brigitte; Matias‑Garcia Pamela R.; Lyytikäinen Leo‑Pekka; Ceder Tiina; Mononen Nina; Rathmann Wolfgang; Winkelmann Juliane; Peters Annette; Kähönen Mika; et al. (BMC, 2022)
Background
Non-coding RNA 886 (nc886) is coded from a maternally inherited metastable epiallele. We set out to investigate the determinants and dynamics of the methylation pattern at the nc886 epiallele and how this methylation status associates with nc886 RNA expression. Furthermore, we investigated the associations between the nc886 methylation status or the levels of nc886 RNAs and metabolic traits in the YFS and KORA cohorts. The association between nc886 epiallele methylation and RNA expression was also validated in induced pluripotent stem cell (iPSC) lines.
Results
We confirm that the methylation status of the nc886 epiallele is mostly binomial, with individuals displaying either a non- or hemi-methylated status, but we also describe intermediately and close to fully methylated individuals. We show that an individual's methylation status is associated with the mother's age and socioeconomic status, but not with the individual's own genetics. Once established, the methylation status of the nc886 epiallele remains stable for at least 25 years. This methylation status is strongly associated with the levels of nc886 non-coding RNAs in serum, blood, and iPSC lines. In addition, nc886 methylation status associates with glucose and insulin levels during adolescence but not with the indicators of glucose metabolism or the incidence of type 2 diabetes in adulthood. However, the nc886-3p RNA levels also associate with glucose metabolism in adulthood.
Conclusions
These results indicate that nc886 metastable epiallele methylation is tuned by the periconceptional conditions and it associates with glucose metabolism through the expression of the ncRNAs coded in the epiallele region.